Promise keeping and reliance damage - Sengupta, Arjun; Vanberg, Christoph (European economic review, 2023)
This paper experimentally investigates the hypothesis that promise-keeping behavior is affected by the “reliance damage” that a counterpart would suffer as a result of a breach. Reliance damage is defined as the difference between the counterfactual benefit that the counterpart would have obtained had they not relied on the promise and that which they would obtain following a breach. We discuss two motivational mechanisms that could drive such an effect. One is that people intrinsically dislike causing reliance damage per se. The other is that people dislike causing regret in another person. We experimentally test these ideas in the context of an experimental trust game. Our evidence is consistent with the hypothesis that promise keeping is affected by reliance damage, and that the underlying mechanism involves a desire not to cause regret in others.
Online verfügbar 21 November 2022, Artikelversion 12 Dezember 2022
Gesehen am 27.01.2023